Evaluating the Impact of TikTok Promotions on Online Shops: Literature Study Approach - Hanum, Latifah; Saputri, Ridho; Ningsih, Yeni; Armayanti, Nabilla; Nofirda, Fitri (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research analyzes the impact of promotion via TikTok on online shops and finds that using TikTok as a promotional tool has a significant positive effect. TikTok, with its appeal of creative and interactive short video content, allows online shop owners to reach a wider audience and increase their brand exposure. The results of this research show good improvements in terms of brand awareness, sales growth, and stronger relationships between customers and brands. In addition, TikTok provides an ideal platform for promotions that attract shopper attention, such as discounts and free shipping. Thus, this research confirms that promotion via TikTok is an effective strategy and has a positive impact on online shops in expanding their market share and increasing their sales results.